“Brought up to Live Double Lives”: Intelligence and Espionage as Literary and Philosophical Figures in Ciaran Carson’s Exchange Place and For All We Know - Czemiel, Grzegorz (Text Matters: A Journal of Literature, Theory and Culture, 2021)
The article examines the figure of the spy—alongside themes related to espionage—as employed in two books by the Northern Irish writer Ciaran Carson (1948–2019): the volume of poems For All We Know (2008) and the novel Exchange Place (2012). Carson’s oeuvre is permeated with the Troubles and he has been hailed one of key writers to convey the experience of living in a modern surveillance state. His depiction of Belfast thematizes questions of terrorism, the insecurity and anxiety it causes in everyday life, as well as the unceasing games of appearances and the different ways of verifying or revising identities. In Carson’s later work, however, these aspects acquire greater philosophical depth as the author uses the themes of doubles, spies, and makeshift identities to discuss writing itself, the construction of subjectivity, and the dialogic relationship with the other. Taking a cue from Paul Ricoeur’s and Julia Kristeva’s conceptions of “oneself as another,” the article examines how Carson’s spy-figures can be read as metaphors for processes of self-discovery and identity-formation, tied to the notion of “self-othering.” Carson employs the figure of the spy—who juggles identities by “donning” different clothes or languages—to scrutinize how one ventures into the dangerous territory of writing, translation and love, as well as to reconsider notions of originality and self-mastery. Ultimately, Carson conceptualizes literature as specially marked by deceptions and metamorphoses, defining in these terms the human condition.